Pengaruh Model Pembelajaran Problem Posing terhadap Hasil Belajar Matematika (Studi Kasus: Siswa Kelas V MI Nurul Huda Lengkong) - Azimah, Khoridatul; zawawi, irwani; suryanti, sri (Universitas Muhammadiyah Gresik, 2023)
Learning at MI Nurul Huda Lengkong is still centered on educators which has an impact on student learning outcomes because students rarely solve problems independently. There needs to be an improvement in learning models to improve student learning outcomes. The learning model that can create an atmosphere of students who are free, creative, and independent in accordance with their abilities is the problem posing learning model. Problem posing is a learning model that requires students to compile questions or break down a problem into simpler questions and refer to solving the problem. The purpose of this model is to create a more interactive learning atmosphere and improve student learning outcomes. This research is quantitative correlational research. To find the influence between problem posing learning models on research learning outcomes using this type of experiment, by comparing the learning outcomes of problem posing and conventional learning. From the research that has been done, the average posttest score of the control class was 58.25 from 8 students and the experimental class was 81.625 from 8 students. This indicates that the problem posing learning model has an influence on improving the learning outcomes of grade 5 MI Nurul Huda Lengkong students.